2010
DOI: 10.1002/cncr.25222
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for melanoma in children and adolescents

Abstract: BACKGROUND: Cutaneous melanoma in childhood is rare; therefore, its prognostic factors and biologic behavior and the effectiveness of adjuvant diagnostic techniques in this group remain mostly unknown. METHODS: The authors conducted a retrospective, observational study on the prognostic significance of clinical and pathologic findings from 137 cutaneous and mucosal melanomas in patients aged <18 years that were reviewed by the pathology department of a large cancer center during the period from 1992 to 2006. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
2
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 55 publications
(87 reference statements)
3
31
2
6
Order By: Relevance
“…Оказалось, что общая десятилетняя выживаемость этих больных статистически достоверно зависе-ла от их возраста: при среднем значении данно-го показателя 80,6% для всех пациентов в группе больных не старше 10 лет он составил 100%, в группе старше 10, но не более 15 лет -69,7%, а среди больных старше 15 и до 20 лет включитель-но -79,5%. Ранее аналогичную тенденцию выяви-ли S. Paradela и соавт., проведя ретроспективный анализ 137 случаев МК, а также меланомы слизи-стых оболочек у пациентов в возрасте до 18 лет [14]. Результаты исследования указывают на раз-личия в биологической структуре МК, возникаю-щей у молодых пациентов, относящихся к разным возрастным группам.…”
Section: патогенезunclassified
See 1 more Smart Citation
“…Оказалось, что общая десятилетняя выживаемость этих больных статистически достоверно зависе-ла от их возраста: при среднем значении данно-го показателя 80,6% для всех пациентов в группе больных не старше 10 лет он составил 100%, в группе старше 10, но не более 15 лет -69,7%, а среди больных старше 15 и до 20 лет включитель-но -79,5%. Ранее аналогичную тенденцию выяви-ли S. Paradela и соавт., проведя ретроспективный анализ 137 случаев МК, а также меланомы слизи-стых оболочек у пациентов в возрасте до 18 лет [14]. Результаты исследования указывают на раз-личия в биологической структуре МК, возникаю-щей у молодых пациентов, относящихся к разным возрастным группам.…”
Section: патогенезunclassified
“…О сходстве сообщили Livestro и соавт., выявившие одинаковую выживаемость молодых и взрослых больных МК в случаях, если пациенты имели первичную опухоль равной толщины; те же авторы, однако, выявили достоверно более высо-кую частоту метастазирования МК у детей и под-ростков в лимфатические узлы по сравнению с таковой у взрослых больных [28]. Установлено, что общая десятилетняя выживаемость молодых боль-ных МК достоверно колеблется в зависимости от их возраста [12,14]. Неодинаковая метастатиче-ская активность МК у пациентов разных возраст-ных групп и разная выживаемость больных МК, являясь интегральными характеристиками опухоли, по-видимому, отражают различия в молекулярном фенотипе меланомы у данных категорий наблюда-емых.…”
Section: диагностикаunclassified
“…4,7,8,1122 Despite the higher rate of nodal disease in pediatric patients, SEER-based and case-matched studies on pediatric melanoma have shown survival rates similar to those seen in adults with melanoma. 6,13 These observations suggest that the biology of melanoma in children may be different from melanoma in adults.…”
mentioning
confidence: 99%
“…The use of biological response modifiers like Interferon-α in melanoma have been reported to affect adults with melanoma. 33 However, our small group of children with melanoma generally reported the highest HRQL outcomes across diagnostic groups at all time-points. These responses provide an insight into the general tolerance of melanoma treatment in adolescents with cancer (15 out of 23 participants in the melanoma group were adolescents).…”
Section: Aimmentioning
confidence: 66%
“…Optimal treatment for melanoma is complete surgical removal and is dependent upon the size, site, level of invasion into the skin and stage of the tumor. 33 Prognosis for resected superficial melanomas is approximately 90%, with patients surviving 10 years from diagnosis. Survival is decreased if the melanoma has spread to distant organs.…”
mentioning
confidence: 99%